INOVASI SIRSAK JAMBE DALAM MENINGKATKAN KOMPETENSI DASAR KADER KESEHATAN DI PUSKESMAS KALIJAMBE - Suyadi; Suharti; Amieratunnisa , Aniesah; Prihandana , Gregorius Raditya Indra (LPPM Universitas Awal Bros, 2025)
Community health cadres often struggle to access fast, accurate, and easy-to-understand information while performing their duties, largely due to irregular training and limited access to updated learning materials. To address this issue, Kalijambe Public Health Center developed Sirsak Jambe, a WhatsApp-based chatbot designed to provide essential competency materials in a practical and flexible format. This descriptive qualitative study involved interviews with health center staff and cadres to assess the implementation of Sirsak Jambe using three dimensions of digital innovation: product, environment, and organization. The findings show that Sirsak Jambe is easy to use, responsive, and provides concise, reliable content that helps cadres quickly solve problems encountered in the field. The social and technological environment of the area supports its use, although challenges remain related to internet connectivity and varying digital literacy levels. Organizational support, staff capacity, and an innovative work culture further enhance implementation, though formal SOPs and regular updates are still needed. The study concludes that Sirsak Jambe is a relevant and beneficial digital solution for improving cadres’ basic competencies, yet its sustainability requires strengthened management and continuous support.